Implementation of Lean Manufacturing with the Takt Time and FMEA Methods to Identify Waste in the Sterile Production Process in the Pharmaceutical Industry - Tatun Uswatun Hasanah; Tita Wulansari; Tryana Putra; Muchammad Fauzi (School of Industrial and System Engineering, Telkom University, 2020)
Pharmaceutical companies is one of the companies engaged in the pharmaceutical sector in Indonesia, as aleading pharmaceutical company in Indonesia and trusted by many people, pharmaceutical companiesalways strives to provide the best service in terms of meeting market demand (customer), delivered on time(lead time). The requests received always vary every month, a drastic increase in the number of demandswill affect the processing time needed to fulfill the demand with the production processing time of aproduct. This problem can be overcome by analyzing the Takt Time and Cycle Time needed to fulfillrequests for October 2020, where the number of requests for product A in October 2020 is 10,560 pcs. Theresults of the analysis of Fast Time and Cycle Time waste using the FMEA method. There are 3 types ofwaste, namely waste of waiting time, unnecessary supplies, and scheduling.